2003
DOI: 10.1007/s00213-003-1474-2
|View full text |Cite
|
Sign up to set email alerts
|

Response to alcohol in females with a paternal history of alcoholism

Abstract: The results of the present study suggest that FHP women may have a reduced response to alcohol on some measures, but FHP women report greater positive effects on other measures. Overall, the differences between FHP and FHN women are subtle compared to the previous studies demonstrating a reduced response to alcohol in FHP men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 61 publications
(67 reference statements)
4
34
4
Order By: Relevance
“…Several studies support our finding that performance in the DAT, PVT and PBT is sensitive to low or moderate BACs (e.g., Evans and Levin, 2003, 2004; Howard et al 2007; Leung et al 2012; McCaul et al 2000; Moskowitz and Robinson 1988; Moskowitz and Florentino 2000; Ogden and Moskowitz 2004; Roehrs et al 2003). Furthermore, the failure of the CST to show any effects of alcohol is in line with recent findings that performance in a similar test (i.e., TMT - part B) was only impaired at a very high BAC (i.e., 1.2 g/L), but not at lower BACs (i.e., 0.5 and 0.8 g/L) as used in the present study (Dry et al 2012).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Several studies support our finding that performance in the DAT, PVT and PBT is sensitive to low or moderate BACs (e.g., Evans and Levin, 2003, 2004; Howard et al 2007; Leung et al 2012; McCaul et al 2000; Moskowitz and Robinson 1988; Moskowitz and Florentino 2000; Ogden and Moskowitz 2004; Roehrs et al 2003). Furthermore, the failure of the CST to show any effects of alcohol is in line with recent findings that performance in a similar test (i.e., TMT - part B) was only impaired at a very high BAC (i.e., 1.2 g/L), but not at lower BACs (i.e., 0.5 and 0.8 g/L) as used in the present study (Dry et al 2012).…”
Section: Discussionsupporting
confidence: 68%
“…Finally, our finding that the DSST shows impairment at a BAC of 0.8 g/L, but not below is in line with most previous studies. All studies have shown impairment at BACs of 0.8 g/L or more, but results are not consistent at BACs between 0.4 and 0.6 g/L ( Brasser et al 2004; Brumback et al 2007; Dumont et al, 2008; Evans and Levin 2003, 2004; Holdstock and de Wit 2001; King and Byars 2004; McCaul et al 2000). …”
Section: Discussionmentioning
confidence: 99%
“…The findings are consistent with most previous data on daughters of alcoholics. These earlier investigations often involved small samples (e.g., Evans and Levin, 2003;Lex et al, 1988Lex et al, , 1994Savoie et al, 1988;, or evaluated the similarity between sons and daughters of alcoholics without directly comparing FHP and FHN women (e.g., Schuckit et al, 2004). While these studies indicated that a low LR was more likely to be observed in FHP compared to FHN women, this is the first investigation to support this conclusion where the women were carefully matched on variables that may affect LR (e.g., age, drinking history), while also minimizing the effect of other factors that are possibly related to the risk for AUDs (e.g., Asian background).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the daughters of alcoholics had a trend for lower subjective ratings of intoxication and less alcohol-induced body sway than FHN women, however, reflecting the small number of FHNs, these group differences were not significant . Most recently, a larger scale evaluation of 16 pairs of FHP and FHN women matched on age, race, level of education, and current and lifetime patterns of drug use, found that the FHPs had significantly lower LRs to alcohol for the DSST, but were more impaired on immediate digit recall (Evans and Levin, 2003). The FHNs tended to be more impaired on observer ratings of intoxication and on a balance task, although these differences were not significant.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that several studies have failed to find clear support for either (e.g. [14]), have reported null findings (e.g. [15]), and have identified potential confounding factors such as drinking history (e.g.…”
Section: Introductionmentioning
confidence: 99%